2021
DOI: 10.5114/biolsport.2020.97677
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance training intensity on the sleep quality and strength recovery in trained men: a randomized cross-over study

Abstract: Resistance training (RT) variables can affect sleep quality, strength recovery and performance. The aim of this study was to examine the acute effect of RT leading to failure vs. non-failure on sleep quality (SQ), heart rate variability (HRV) overnight and one-repetition maximum (1-RM) performance 24 hours after training. Fifteen resistance-trained male athletes (age: 23.4 ± 2.4 years; height 178.0 ± 7.6 cm; weight: 78.2 ± 10.6 kg) performed two training sessions in a randomized order, leading to failure (4x10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…Fomentando la salud mental, la gestión emocional pre-cama mejorará bajo la mayor presión de sueño, que correlaciona con la menor latencia de inicio (ejercicios mente-cuerpo y aeróbico), permitiendo gozar de una duración del sueño prolongada (Fan et al, 2021;Guan et al, 2021;Xie et al, 2019). Esto se traduce en mayor eficiencia (entrenamiento de fuerza) y en la sensación de haber tenido una buena calidad del sueño subjetiva sin fragmentación (fuerza), promoviendo subsecuentemente la adecuada función diurna (Ramos-Campo et al, 2021;Santiago et al, 2022).…”
Section: Influencia De Los Hábitos Deportivosunclassified
“…Fomentando la salud mental, la gestión emocional pre-cama mejorará bajo la mayor presión de sueño, que correlaciona con la menor latencia de inicio (ejercicios mente-cuerpo y aeróbico), permitiendo gozar de una duración del sueño prolongada (Fan et al, 2021;Guan et al, 2021;Xie et al, 2019). Esto se traduce en mayor eficiencia (entrenamiento de fuerza) y en la sensación de haber tenido una buena calidad del sueño subjetiva sin fragmentación (fuerza), promoviendo subsecuentemente la adecuada función diurna (Ramos-Campo et al, 2021;Santiago et al, 2022).…”
Section: Influencia De Los Hábitos Deportivosunclassified
“…Consequently, daytime napping has been utilized as a strategy to increase the quality and quantity of sleep in athletes [ 17 ]. It has been reported that napping is crucial for supporting nighttime sleep and optimizing physical performance, as the recommended 8 h of sleep per day may not be sufficient for athletes due to their physical and mental demands [ 16 , 18 , 19 , 20 , 21 , 22 , 23 ]. In addition, napping opportunity can positively affect short-term maximal performance, attention, feelings, muscle soreness, fatigue, stress ((no-nap opportunity (N0), 25 min of nap opportunity (N25)) [ 20 ], vigilance, shuttle run performance (N25) [ 24 ], 5 m Shuttle Run Test performance ((no-nap opportunity (N0), 25 min of nap opportunity (N25), a 35 min nap opportunity (N35), a 45 min nap opportunity (N45), a 90 min nap opportunity (N90)) [ 21 , 25 ], repeated sprint performance (a 20 min nap opportunity (N20), a 90 min nap opportunity (N90)) [ 26 ] and sprint performance [ 27 ].…”
Section: Introductionmentioning
confidence: 99%